2014
DOI: 10.1111/cxo.12147
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormones and the dry eye

Abstract: The greater prevalence of dry eye in women compared to men suggests that sex hormones may have a role in this condition. This review aims to present evidence for how sex hormones may affect the ocular structures involved in the production, regulation and maintenance of the normal tear film. It is hypothesised that hormone changes alter the homeostasis of the ocular surface and contribute to dry eye. Androgens impact on the structure and function of the meibomian and lacrimal glands and therefore androgen defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
93
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 188 publications
(534 reference statements)
4
93
0
2
Order By: Relevance
“…Previous research has shown that dry eye is more symptomatic in women and they have greater dissatisfaction with treatment compared to men, probably due to role of sex hormones on autoimmunity. [23][24][25][26] A majority of SS literature has focused on the presentation and/or severity of disease in women, largely because of the relatively small number and highly variable clinical presentation of men with primary SS. 11 We observed a 10:1 female/male ratio, consistent with other large-scale SS studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that dry eye is more symptomatic in women and they have greater dissatisfaction with treatment compared to men, probably due to role of sex hormones on autoimmunity. [23][24][25][26] A majority of SS literature has focused on the presentation and/or severity of disease in women, largely because of the relatively small number and highly variable clinical presentation of men with primary SS. 11 We observed a 10:1 female/male ratio, consistent with other large-scale SS studies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no clinical trial which investigates the corneal and tear function effects of systemic or topical androgen treatment in men have been published. In their latest extensive reviews, Truong et al and Versura et al pointed out the insufficient number of published clinical data about the impact of androgen therapy in dry eye [14,15]. Limited number of studies in men demonstrate that low endogenous androgenic activity especially in men using anti-androgen therapy for prostate cancer may result in ocular surface abnormalities and meibomian gland dysfunction which results in evaporative dry eye [14].…”
Section: Discussionmentioning
confidence: 99%
“…In their latest extensive reviews, Truong et al and Versura et al pointed out the insufficient number of published clinical data about the impact of androgen therapy in dry eye [14,15]. Limited number of studies in men demonstrate that low endogenous androgenic activity especially in men using anti-androgen therapy for prostate cancer may result in ocular surface abnormalities and meibomian gland dysfunction which results in evaporative dry eye [14]. Furthermore, systemic anti-androgen treatment resulted in reduced tear stability, and corneal epitheliopathy [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Hormone replacement therapy may improve aqueous tear production but not the quality of tears in dry eye disease, and the effect on tear production is dependent upon age. 4 Nonetheless, recent studies indicate that hormone replacement therapy can increase the risk of coronary heart disease, stroke, and breast and endometrial cancers.…”
mentioning
confidence: 99%